An intuitionistic fuzzy site selection decision framework for waste-to-energy projects from the perspective of "Not In My Backyard" risk - Yuanlu Qiao; Jingpeng Wang (AIMS Mathematics, 2023)
In the process of site selection for waste-to-energy (WtE) projects, the public is concerned about the impact of project construction on the surrounding environment and physical health and thus resists the construction site, leading to the emergence of "Not In My Backyard" (NIMBY) risk, which hinders the implementation of WtE projects. These risks make the ambiguity and uncertainty of scheme evaluation and decision higher. In this regard, this study constructed a WtE project site selection decision framework based on comprehensive consideration of NIMBY risk. Firstly, indicators were selected from cost perception, benefit expectation, and NIMBY risk to construct a WtE project site selection indicator system. Then, based on the "Decision Making Trial and Evaluation Laboratory" (DEMATEL) and the Intuitionistic Fuzzy Multi-criteria Optimization and Compromise Solution (IFVIKOR) method, a site selection decision framework is constructed. The system takes into account the interaction between indicators and obtains a more reasonable index weight. Meanwhile, the intuitionistic fuzzy theory is used to solve the fuzziness and uncertainty in risk assessment and decision-making. Finally, the feasibility of the siting decision system was verified through case studies. The results show that the A3 in this case was considered the best location for the project. In addition, the sensitivity analysis verifies the reliability and stability of the WtE project location decision framework.